(untitled) (Global Journal of Management and Business Research, 2016)
In spite of the exceptional development of the human community in the last few decades, the present state of development manifests not only increasing differences between parts of human society but also a serious threat to man#x2019;s survival. Numerous problems, as a result of the development to date as well as of the existing present day problems are an indication of the need to change the approach and ways of developing life and work in the human community. The influential factors impacting development include man, science and education, technology and technical sciences, natural resources and socio-political systems. Human development is considered the best alternative in regard to which corresponding goals, criteria and standards are proposed as well as man becoming both the subject and object of development. New development should be pursued in an integral and coordinated manner in all segments of life and work in society.